CAP measures towards environmental sustainability—Trade opportunities for Africa?. Issue 1 (13th March 2021) - Latka, Catharina; Heckelei, Thomas; Kuhn, Arnim; Witzke, Heinz-Peter; Kornher, Lukas
Abstract: Environmental sustainability is a core aspect of the proposed future EU Common Agricultural Policy (CAP). Policy changes must not compromise socioeconomic development in low-income countries, whereas the extensification of EU agriculture may also create trade opportunities abroad. We apply a global agricultural-economic model to assess EU–African trade-related impacts of potential, environmentally motivated CAP changes. Restrictions on livestock density and nitrogen application reveal reduced EU production levels of meat. This lowers the EU's agricultural environmental burden and share in agricultural trade flows to Africa. However, overall food supply in Africa is not projected to deteriorate substantially, as imports from other world regions and increasing domestic production fill the gap. While this weakens the global emission reduction potential, net livestock producers in Africa may benefit from increasing producer prices. How far potentials for domestic production and trade can be used in African regions depends at least partly on their competitiveness vis-á-vis substituting importers.